2018
DOI: 10.1177/0020731418767548
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Social Protection Policies and Programs on Suicide: A Literature Review

Abstract: Despite vigorous interest in showing the association between economic determinants and suicide, not many studies have focused on the social protection that can moderate the detrimental impact of the economic environment on suicide. This article is the first to review the relationship between suicide and social protection. In this article, I summarize the empirical findings and theoretical approaches in published papers on the relationship between suicide and social protection, and I identify knowledge gaps for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Unemployment, poverty and inequalities represent major risk factors for suicide which are considerably exacerbated by the current global crisis. Studies from high-income countries on the association between social protection policies and suicide rates 65 show that the various policies may have a different impact.…”
Section: Mitigating the Impact Of Unemployment Poverty And Inequalitiesmentioning
confidence: 99%
“…Unemployment, poverty and inequalities represent major risk factors for suicide which are considerably exacerbated by the current global crisis. Studies from high-income countries on the association between social protection policies and suicide rates 65 show that the various policies may have a different impact.…”
Section: Mitigating the Impact Of Unemployment Poverty And Inequalitiesmentioning
confidence: 99%
“…A recent review (Kim, 2018) identified seven studies that investigated the relationship between social policy and suicide in the U.S. (Cylus et al, 2014;Flavin and Radcliff, 2009;Minoiu and Andrés, 2008;Ross et al, 2012;Zimmerman, 2002Zimmerman, , 1995Zimmerman, , 1987. These studies present some mixed evidence but overall, they indicate that there is a negative relationship between various forms of social protection and suicide.…”
Section: Suicide Economic Strain and Policymentioning
confidence: 99%
“…The suicide rate for those with a high school education or less appears to be particularly sensitive to increases in the minimum wage, especially during periods of high unemployment ( Kaufman et al, 2020 ). A broad review ( Kim, 2018 ) suggests that social protection policies play some role in moderating the negative effect of the economic environment on suicide.…”
Section: Introductionmentioning
confidence: 99%